Islamisation of human knowledge in the built environment education: a case of the Bachelor of Science in architectural studies, international Islamic university Malaysia - Ahmad Sarkawi, Azila; Abdul Rashid, Khairuddin; Aripin, Srazali; Hasan, Sharina Farihah; Othman, Jamilah (2015)
One of the interpretations of Islamisation of human knowledge is a process of tracing the root of secular knowledge to the origin (ta’seel) of knowledge in Islam that is al-Qur’an and alSunnah. As knowledge and education is indispensable, current scenario of educational dualism that Islam and secular co-exist becomes a matter of concern for Islamisation of human knowledge. Inspired by the University’s vision and mission of becoming a leading world institution with integrated Islamic philosophy, Kulliyyah of Architecture and Environmental Design (KAED), IIUM is materializing Islamisation agenda in the built environment since its inception in 1996 generally and in the courses offered specifically. Thus, it is the aim of the study to measure the level of Islamic inputs and to identify the types of Islamisation modes practiced by the lecturers in their teaching delivery. For that matter, Bachelor of Science in Architectural Studies programme was chosen to represent the built environment body of knowledge. The study deployed a questionnaire survey method to respective lecturers who taught theory courses offered under the programme. The courses were identified from the class schedule produced by the Academic Office of KAED for academic session 2014/2015. Out of 39 courses offered under the programme for that particular academic session, 17 are regarded as theory courses intended for this study. Other courses on graphic skill, computer application, and studio-base are excluded from the survey. The study revealed Islamic input in almost all courses (88%) was average and below, ranging from 7 to 56% and the mode of Islamisation “promoting Islamic perspectives” topping the list. The findings helped the Kulliyyah to garner more Islamic input in the courses through its curriculum review. Besides, training to lecturers on Islamisation in teaching delivery and team teaching with lecturers from Islamic studies department were proposed for better integration and Islamisation of human knowledge.